The prevalence of carotid atherosclerosis in spontaneous populations in Tomsk - Yu V Zhernakova (Системные гипертензии, 2014)
Modern data on the prevalence of carotid atherosclerosis (CAS) in the general population are very limited both in Russia and abroad. In this study we investigated the prevalence of CAS using screening ultrasound examination in a random sample of spontaneous population aged 25-64 years in urbanized city of Western Siberia as part of a multicenter observational study ESSE-RF (epidemiology of cardiovascular diseases in different regions of the Russian Federation).The CAS prevalence was 36,4% in males and 24,4% in women in the examined population. We determined large variation of atherosclerotic plaques prevalence, depending on the age and gender. The CAS prevalence in creased more intense in males up to 50 years and in women 50 up to 59 years. Men were twice as likely to had been diagnosed CAS than women. The prevalence of CAS associated with amount of narrowing less than 25 and 50% or more in the examined population was 68,5%, and less than 1%, respectively. According to the results of the study we shouldpay great attention to the processes, leading to intensive development of CAS in the population aged 35-44 years, especially in men. The development of effective approaches to the control of modifiable risk factors for cardiovascular diseases in this age group could be a very appropriate measure for preventing the rapid development of the CAS in the population.